Re-imagining Curriculum: Spaces for Disruption - McKenna, Sioux (Critical Studies in Teaching and Learning, 2023)
Quinn, L. (ed.) 2019. Re-imagining Curriculum: Spaces for Disruption. Cape Town: Sun Media